COVID-19 vs. Classical Myocarditis Associated Myocardial Injury Evaluated by Cardiac Magnetic Resonance and Endomyocardial Biopsy - Tanacli, Radu; Doeblin, Patrick; Götze, Collin; Zieschang, Victoria; Faragli, Alessandro; Stehning, Christian; Korosoglou, Grigorios; Erley, Jennifer; Weiss, Jakob; Berger, Alexander; Pröpper, Felix; Steinbeis, Fridolin; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background. Despite the ongoing global pandemic, the impact of COVID-19 on cardiac structure and function is still not completely understood. Myocarditis is a rare but potentially serious complication of other viral infections with variable recovery, and is in some cases associated with long-term cardiac remodelling and functional impairment. Aim. To assess myocardial injury in patients, who recently recovered from an acute SARS-CoV-2 infection with advanced cardiac magnetic resonance imaging (CMR) and endomyocardial biopsy (EMB). Methods. In total, 32 patients with persistent cardiac symptoms after a COVID-19 infection, 22 patients with acute classic myocarditis not related to COVID-19 and 16 healthy volunteers were included in this study and underwent a comprehensive baseline CMR scan. Of these, 10 patients post COVID-19 and 13 with non-COVID-19 myocarditis underwent a follow-up scan. In 10 of the post COVID-19 and 15 of the non-COVID-19 myocarditis patients endomyocardial biopsy (EMB) with histological, immunohistological and molecular analysis was performed. Results. In total, 10 (31%) patients with COVID-19 showed evidence of myocardial injury, 8 (25%) presented with myocardial oedema, 8 (25%) exhibited global or regional systolic left ventricular (LV) dysfunction, and 9 (28%) impaired right ventricular (RV) function. However, only 3 (9%) of COVID-19 patients fulfilled updated CMR - Lake Louise criteria (LLC) for acute myocarditis. Regarding EMB, none of the COVID-19 patients, but 87% of the non-COVID-19 myocarditis patients presented histological findings in keeping with acute or chronic inflammation. COVID-19 patients with severe disease on the WHO scale presented with reduced biventricular longitudinal function, increased RV mass and longer native T1 times compared with those with only mild or moderate disease. Conclusions. In our cohort, CMR and EMB findings revealed that SARS-CoV-2 infection was associated with relatively mild but variable cardiac involvement. More symptomatic COVID-19 patients and those with higher clinical care demands were more likely to exhibit chronic inflammation and impaired cardiac function compared to patients with milder forms of the disease.